The boreal ecosystem - Larsen, James Arthur (Academic Press, 1980)
The Boreal Ecosystem presents an overview of the state of knowledge on the boreal forest region of North America, with extensive reference to the boreal regions of Europe and Asia. Initial sections of this book deal with aspects of the floristic composition and evolutionary history of the boreal vegetation. These introduce subsequent discussions on the processes at work in vegetation, soils, and the atmosphere-in short, with the boreal forest as an ecosystem, the sum total of the influences of many closely interlaced biotic and physical factors. These include not only plant species that make.